Knowledge, Attitudes, and Practices of Tourism and Hospitality Management Students towards Innovative Plastic Waste Management using Solar Energy - Abad, Mark Alvin H.; Reyes Jr., Roberto V. (International Review of Management and Marketing, 2025)
The primary objective of this study was to evaluate the plastic waste management knowledge, attitudes, and practices among tourism and hospitality management students at Nueva Ecija University of Science and Technology. The study involved 292 participants thru mixed method techniques. Significant results presented the potential to contribute towards the formulation of effective strategies and interventions aimed at reducing plastic waste and promoting recycling in the tourism and hospitality industry. Moreover, the research explored the feasibility of designing an innovative solar-powered pot-making machine for transforming plastic waste, specifically within educational institutions. This endeavor aligns with the global movement towards sustainable technologies and the principles of a circular economy.